### Vertical Translations of Sine and Cosine graphs

##### Example

##### Problem 1

This translation expresses a vertical shift downwards by 1.

##### Problem 2

##### Problem 3

Graph of f(x) = sin (-x) is the reflection of the graph of f(x) = sin (x) about x-axis.

Each pair of corresponding points on the graphs has the same distance form the x-axis.

For example, points A and B are two corresponding points on the graphs, and they are at the same distance from the x-axis. That is, AM = BM.

##### Problem 4

The difference between the variables of the two functions is:

$$\left(x+\frac{5\pi}{4} \right)-\left(x+\frac{\pi}{4} \right)$$

= $$x+\frac{5\pi}{4} -x-\frac{\pi}{4}$$

= $$\frac{5\pi}{4} -\frac{\pi}{4}$$

= $$\frac{4\pi}{4}$$

= $$\pi$$

So, the graph of f(x) is transferred $$\pi $$ units to the left to create the graph of g(x).

##### Problem 5

The difference between the variables of the two functions is:

$$\left(3x+\frac{\pi}{3} \right)-\left(3x-\frac{\pi}{3} \right)$$

= $$3x+\frac{\pi}{3} -3x+\frac{\pi}{3}$$

= $$\frac{\pi}{3} +\frac{\pi}{3}$$

= $$\frac{2\pi}{3}$$

Therefore, the graph of f(x) is transferred $$\frac{2\pi}{3} $$ units to the left to generate the graph of g (x)

##### Problem 6

Difference between the values of f(x) and g(x) is -3. Therefore, g(x) is obtained by moving f(x) 2 units downward.

##### Problem 7

First graph of $$f(x)=\sin (x)$$ is transferred to the graph of $$h(x)=\sin (x+2)$$ by moving 2 units to the left as shown in the graph below.

Then the graph of g(x) is obtained by moving the graph of h(x) upward 2 units.

##### Problem 8

Graph of cos (-x) is exactly the same as the graph of cos (x).

So, g(x) is exactly the reflection of f(x) about x-axis.

##### Problem 9

$$g(x)-f(x)=\left[\cos \left(x-\frac{5\pi}{3} \right)-\frac{5\pi}{3} \right] - \cos \left(x-\frac{5\pi}{3} \right)$$

= $$\cos \left(x-\frac{5\pi}{3} \right)-\frac{5\pi}{3} -\cos \left(x-\frac{5\pi}{3} \right)$$

= $$-\frac{5\pi}{3} $$

So, the graph of f(x) is moved $$\frac{5\pi}{3} $$ units downward to generate the graph of g(x).

##### Problem 10

$$f(x)=\cos \left(\pi -x\right)$$ is the same as $$f(x)=\cos \left(x-\pi \right)$$. So $$g(x)=-\cos \left(x-\pi \right)$$ is the reflection of f(x) about x-axis.

##### Problem 11

$$g(x)=\cos \left(\frac{\pi}{3} \, \, -\, \, x\right)\, \, -\, \, \frac{\pi}{3} $$ is the same as $$g(x)=\cos \left(x-\frac{\pi}{3} \, \, \right)\, \, -\, \, \frac{\pi}{3} $$.

So, f(x) is moved downward $$\frac{\pi}{3} $$ units.

##### Problem 12

$$(3x+3\pi)-(3x-2\pi)$$

= $$3x+2\pi -3x+3\pi$$

= $$2\pi +3\pi$$

= $$5\pi$$

So, the graph of f(x) moved $$5\pi $$ units to the left in order to generate the graph of g(x).